Phytochemical assay, potential of antimalarial and antioxidant activities of green tea extract and its fraction - Fanny Rahardja (Biomedical Engineering, 2015)
Objective : The research objective was to evaluate the phytochemical compounds, theantioxidant and anti-malarial activity of green tea extract and its fraction.Methods : The antioxidant activity were measured by 1,1-diphenyl-2-picryl-hydrazyl (DPPH)scavenging activity used in vitro laboratories prospective experimental design and completelyrandomized design, using ethanol extract, hexane, ethyl acetate, butanol fraction, and waterfraction of green tea in 7 levels of concentration compared to epicatechin (EC). The data wereanalyzed using linear regression analysis, and were continued by determined InhibitoryConcentration50 (IC50). The anti-malarial activity of green tea fractions were compared toartemisinin. The data were analyzed using probit analysis, and were continued by determinedIC50 .Result: The results showed that the highest antioxidant activity (IC50) was the fraction of ethylacetate 2,184 μg/ml. The anti-malarial activity IC50of water and ethyl acetate fraction, ethanolextract and butanol fraction were 0,000090 μg/mL,0,003 μg/mL, 0,006 μg/mL, 0,011 μg/mlrespectively.Conclusion : Extract and fractions of green tea have potential anti-malarial and antioxidantproperties.